(untitled) (Annual of the Faculty of Philosophy in Skopje, 2021)
The world in the 21st century has proven to be a dangerous and unsafe place to live full of unpredictable threats and risks that vary in form and intensity of manifestation. Due to the unpredictable trajectory of the dangers, there is a need to obtain timely, accurate, and verified intelligence data on the situation in certain regions and countries. Thus the modern intelligence services whose primary role is to protect the state and its vital interests from various types of security threats and risks were developed. Hence, we will analyze the process of reforms in the security-intelligence sector as an important segment for the integration of R.N.Macedonia in the Euro-Atlantic structures. At the same time, we will perceive the place and role that the security and intelligence services have as key entities in the national security system of the Republic of North Macedonia in order to take preventive and repressive measures in the fight against modern threats, as well as their legal competencies in the field of security and intelligence.